New approach for planning the mountain bike training with virtual coach - Rauter, Samo (Akademia Wychowania Fizycznego w Poznaniu)
Virtual technologies make a big step forward also in the world of mountain bike sport. Monitoring the progress of performances during sports training is the eternal desire of each competitive mountain biker. They can measure or analyse data directly from their trainings. As some previous study shows some sophisticated data analytical methods such as data mining are becoming increasingly useful tools in analysing sport performance and also by supporting decision making. For example on the basis of this specific data it is able to create algorithm for planning the sport specific training sessions. In this way sport applications may help also coaches to develop more sophisticated training program for their athletes. All this virtual technologies has led to the idea that they can put the concept of a complex computer system, which is virtual coach, which is based on the principle of cyclization/periodization of sports training. That will be also main focus in our study to show how virtual coaching may work for example for endurance athletes in our case mountain bikers.
Keywords: virtual coach; new technologies; mountain bike; sport training